1998
DOI: 10.1007/s004280050205
|View full text |Cite
|
Sign up to set email alerts
|

Survival and cardiovascular pathology of heterozygous Watanabe heritable hyperlipidaemic rabbits treated with pravastatin and probucol on a low-cholesterol (0.03%)-enriched diet

Abstract: This study was aimed at determining the effects of a combined pravastatin and probucol regimen on survival and vascular pathology of heterozygous Watanabe heritable hyperlipidaemic (WHHL) rabbits fed a low-cholesterol (0.03%)-enriched diet. Pravastatin monotherapy preceded the combined treatment. In animals receiving pravastatin and the enriched diet (verum group; n = 6), mean total serum cholesterol levels were consistently lowered at a dosage of 5 mg/kg pravastatin and with the combined treatment. Survival w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Given its preponderance, this increase in collagen can explain why probucol, overall, increased lesion size at the sinus. Our findings are consistent with previous reports on compositional changes caused by probucol in coronary arteries of hypercholesterolemic rabbits 14,15 and nonhuman primates. 13 Total cell numbers, the percentages of lesion comprised of macrophages (M) and extracellular matrix (ECM), and mRNA for F4/80 antigen were determined as described in the Methods section.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Given its preponderance, this increase in collagen can explain why probucol, overall, increased lesion size at the sinus. Our findings are consistent with previous reports on compositional changes caused by probucol in coronary arteries of hypercholesterolemic rabbits 14,15 and nonhuman primates. 13 Total cell numbers, the percentages of lesion comprised of macrophages (M) and extracellular matrix (ECM), and mRNA for F4/80 antigen were determined as described in the Methods section.…”
Section: Discussionsupporting
confidence: 94%
“…Importantly, these changes are associated with a more stable plaque type, less vulnerable to rupture, and in the rabbit have been reported to increase survival. 15 Therefore, the action of probucol at the aortic sinus in apoE Ϫ/Ϫ , and possibly also LDL receptor Ϫ/Ϫ , 31 mice may be considered beneficial rather than pro-atherogenic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that in previous studies heterozygous WHHL rabbits showed spontaneous atherosclerotic lesions [10]which were not observed until at least 2 years of age [11]. In heterozygous WHHL from another breeding, serum cholesterol levels in the range of those from control NZW fed a standard diet were found so that a 0.03% cholesterol-enriched diet was needed to facilitate lesion development [12, 13]. We can speculate that, due to spontaneous selection, there is a more or less remarkable deficit in the hepatic LDL receptor in inbred animals which in turn makes heterozygous WHHL rabbits more or less prone to developing early lesions.…”
Section: Discussionmentioning
confidence: 99%